2013
DOI: 10.1002/dac.2520
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of S‐MAC protocol

Abstract: SUMMARYWireless sensor networks have been developed in the way of higher speed, more stability, and more energy efficiency in recent years. Because most wireless sensors are powered by energy‐constrained batteries, efficient energy consumption plays the most important role in the design of wireless sensor networks. For energy efficiency, aside from economizing the use of power in the sensor hardware, extensive research efforts have been dedicated towards designing energy‐efficient protocols in the MAC layer. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…While most of the energy‐efficient MAC protocols for WSNs had taken pure experimental approaches, few works have attempted to model and analyze MAC protocols. First, the analytical model of well‐known low duty‐cycle protocols, B‐MAC, X‐MAC, and SMAC, has been derived by Polastre et al Buettner et al and Chang et al respectively. The most relevant work to this one is by Langendoen and Meier, who have attempted to model and analyze energy consumption and average latency of some MAC protocols, while considering traffic and network models for very low data rate applications.…”
Section: Related Workmentioning
confidence: 99%
“…While most of the energy‐efficient MAC protocols for WSNs had taken pure experimental approaches, few works have attempted to model and analyze MAC protocols. First, the analytical model of well‐known low duty‐cycle protocols, B‐MAC, X‐MAC, and SMAC, has been derived by Polastre et al Buettner et al and Chang et al respectively. The most relevant work to this one is by Langendoen and Meier, who have attempted to model and analyze energy consumption and average latency of some MAC protocols, while considering traffic and network models for very low data rate applications.…”
Section: Related Workmentioning
confidence: 99%
“…There exist works (e.g., ) on the study of performance of terrestrial wireless sensor network under different scenarios. Unlike terrestrial wireless sensor network, UWASNs are subjected to increased challenges because of adverse conditions of underwater channel.…”
Section: Related Work and Contributionmentioning
confidence: 99%
“…Additionally, a recursive approach capable of calculating the mean access delay has been proposed in [3]. Paper [19] thoroughly analyzed the performance of sensor medium access control (S-MAC) scheme, which is a popular energy-efficient MAC protocol; this paper conducts the performance analysis of S-MAC protocol, where the mathematical equations for the saturation throughput analysis of S-MAC protocol are derived and verified experimentally. Only the research works in [14,15] have be reported to improve the scheduler of the HCF to enhance the performance of the network by archiving the delay upper bound for a large range of traffic load.…”
Section: Related Workmentioning
confidence: 99%
“…However, the HCCA mechanism has been rarely addressed because of its inflexibility using centralized control and assignment infrastructure. [19] Paper [20] presents an adaptive packet scheduling scheme for 802.16e networks; this paper uses a cross-layer approach and the states of the bandwidth request queues in the base station (BS) to limits the maximum delay to the real-time applications; this simulation results shows satisfactory results [20]. On the other hand, the work in [16] has proposed an analytical model for ad hoc networks, and it has also proposed a scheme to maximize the network throughput by tuning the initial contention windows size.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation